Effectiveness of a distance-learning vs standard training in the integrated management of childhood illnesses: a cluster randomized controlled trial - Saidul Abrar; Assad Hafeez; Sana Rahim; Suhail A. R. Doi; Muhammad Naseem Khan (BMC Public Health)
Abstract Background The Integrated Management of Childhood Illnesss (IMCI) strategy has a lower coverage. The World Health Organization (WHO) introduced the concept of distance learning IMCI in 2014 to improve uptake of the strategy. This study was conducted to evaluate the effectiveness of a distance learning IMCI training compared with the standard IMCI training in the correct management of children presenting to primary health centers. Methods This cluster randomized controlled trial with a 1:1 parallel design was conducted at 26 Basic Health Units (BHUs) in Pakistan. Healthcare workers in BHUs (n = 13) randomized to the intervention arm were trained as per the dIMCI protocols while those (n = 13) randomized to the control arm were trained as per the standard protocol. The trained heathcare workers were followed for around five months and were evaluated in the management of childhood illnesses at their respective health facilities. Correct management, the principal outcome, was defined based on a case being correctly assessed (proficiency score of ≥ 6 out of the total score of 10), classified (compared to the gold standard physician), treated (compared to the gold standard physician), and counseled (proficiency score of ≥ 5 out of the total score of 7). Descriptive statistics, binary logistic regression, and 95% confidence interval were calculated using Stata version 18 adjusted for the clusters. P-values < 0.05 were regarded as significant. Results Under-five children presented to the two arms were mostly similar in gender, age, duration of consultation with the healthcare worker, and presenting complaints. On logistic regression, the dIMCI training was found to be a significant factor in the correct classification (OR = 1.77, 95% CI 1.22—2.58), correct counseling (OR = 6.11,95% CI 3.06 – 12.19), and the overall management of children (OR = 3.35, 95% CI 2.03 – 5.52) with strong evidence against the model hypothesis at this sample size. The dIMCI training showed weak evidence against the model hypothesis in the domains of correct assessment (OR = 1.84, 95% CI 0.99—3.40) and correct treatment (OR 1.46, 95% CI 0.92 – 2.31). Conclusions Health policymakers could consider the dIMCI an effective, feasible, and flexible alternative to standard IMCI training for scaling up the IMCI strategy. Trial registration Registered with www.chictr.org.cn , under ChiCTR1900027201 on 05/11/2019.